Application of Information and Communication Technology in Improving the Quality of Learning (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This research is based on delays in developing the quality of the learning process which results in low student learning outcomes, especially at the basic education level. Thus, through scientific studies in this research, using an exploratory qualitative approach, as well as case studies in superior schools, the results are as follows: (1) a periodic, continuous and sustainable optimization project is needed to develop teachers' abilities in the process of implementing ICT in the learning process , until reaching the advanced category from three categories (advanced, independent and needs guidance); (2) Most of the obstacles faced by teachers originate from the availability of school expenditure budgets, so school principals need special strategies in the process of extracting budgets for spending on facilities and accommodation for activities; (3) Indicators of the success of ICT application in the learning process are aimed at indicators: (a) quality of the ICT application process; (2) impact on students' learning process activities; and (3) increasing student learning outcomes. (4) developing strategies for implementing ICT in the learning process including: (a) Strategic planning for facility preparation; (2) Effectiveness of ICT application in the learning process; (3) the effectiveness of the principal's clinical supervision; (4) Implementation of a technology quality culture in schools; and (5) Sustainable development.